2010
DOI: 10.2319/121009-709.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sites for orthodontic mini-implant placement assessed by cone beam computed tomography

Abstract: Objectives: To determine (1) the optimal sites for mini-implant placement in the maxilla and the mandible based on dimensional mapping of the interradicular spaces and cortical bone thickness and (2) The effect of age and sex on the studied anatomic measurements. Material and Methods: The cone beam computed tomography images of 100 patients (46 males, 54 females) divided into two age groups (13-18 years), and (19-27 years) were used. The following interradicular measurements were performed: (1) Buccolingual bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
108
3
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 17 publications
21
108
3
13
Order By: Relevance
“…The thickness of the alveolar cortical bone was found to be often less than 1 mm buccally in the entire maxilla and anteriorly in the mandible, corroborating earlier reports. 5,7,[10][11][12] Thus, the accuracy of the micro-CT measurements was high Figure 3a. Sinus perforation can occur during mini-implant insertion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thickness of the alveolar cortical bone was found to be often less than 1 mm buccally in the entire maxilla and anteriorly in the mandible, corroborating earlier reports. 5,7,[10][11][12] Thus, the accuracy of the micro-CT measurements was high Figure 3a. Sinus perforation can occur during mini-implant insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Different references have been used for measuring the thickness of the cortical bone, eg, the palatal plane, 12 the Frankfort horizontal plane, 13 the occlusal plane, 7 the mandibular plane, 8 the perpendicular to the bone surface, 10,11 of the local insertion site and the long axis of adjacent teeth. 5,6 We opted for the latter method because it seems to be clinically applicable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Thus, placement in interdental spaces restricts the choice of placement sites, biomechanics of orthodontic treatment, and size of mini-implants as the spaces are not always adequate to accommodate mini-implants with varying dimensions. 23 It is therefore recommended that for placement in interradicular spaces, implants should be smaller than 1.5 mm in diameter and 6 mm in length. 21,24 The commercial design used in this study has these dimensions and showed significantly compromised stability compared with the new designs (N1 and N2).…”
Section: Discussionmentioning
confidence: 99%
“…Buccolingual thickness and cortical bone thickness were also obtained to determine the dimensions of the required implants. 4 Orthodontic mini-implants with sizes 1.5 × 11.6 mm were placed (Aarhus mini-implants, Denmark), one in the buccal and one in the palatal region of the 26 (Fig. 5).…”
Section: Mini-implant Placement In the Maxillamentioning
confidence: 99%